BLOOM’S TAXIONOMY AND DIDACTIC SIGNIFICANCE OF CRITICAL THINKING METHOD IN THE EDUCATIONAL PROCESS - Rakhmonova , Shakhnoza; Rakhmatov , Bekzod (Innovative Development in Educational Activities, 2023)
This article explores the use of Bloom’s Taxonomy and critical thinking methods in the educational process. Bloom’s Taxonomy is a widely used framework that categorizes educational goals and objectives by their complexity and specificity. The cognitive domain of the taxonomy includes six levels of learning, ranging from simple recall to more complex skills such as analysis, synthesis, and evaluation. Critical thinking methods can be applied at all levels of instruction, promoting the development of higher order thinking skills and metacognitive skills such as self-regulated learning and reflection. The didactic significance of critical thinking methods lies in their ability to engage students in complex and meaningful learning experiences, promoting lifelong learning and personal growth. The article emphasizes the importance of incorporating Bloom’s Taxonomy and critical thinking methods in education to promote a more meaningful and fulfilling educational experience.